How will drivers take back control in automated vehicles? A driving simulator test of an interleaving framework - Nagaraju, Divyabharathi; Ansah, Alberta; Al Nahin Ch, Nabil; Mills, Caitlin; Janssen, Christian P.; Shaer, Orit; Kun, Andrew L. (Association for Computing Machinery, 2021)
We explore the transfer of control from an automated vehicle to the driver. Based on data from N=19 participants who participated in a driving simulator experiment, we find evidence that the transfer of control often does not take place in one step. In other words, when the automated system requests the transfer of control back to the driver, the driver often does not simply stop the non-driving task. Rather, the transfer unfolds as a process of interleaving the non-driving and driving tasks. We also find that the process is moderated by the length of time available for the transfer of control: interleaving is more likely when more time is available. Our interface designs for automated vehicles must take these results into account so as to allow drivers to safely take back control from automation.
Keywords: Automated driving; Interleaving framework; Transfer of control; Taverne; Artificial Intelligence; Human-Computer Interaction; Automotive Engineering